1919
DOI: 10.1097/00000441-191910000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Injection of Atropin on the Pulse-Rate, Blood-Pressure and Basal Metabolism in Cases of “Effort Syndrome.”

Abstract: STURGIS, WEARN, TOMPKINS'. ATROl'IN IN EFFORT SYNDROME discrete and in one instance confluent miliary nodules in the paren¬ chyma, lesions that can be correctly estimated as of recent develop¬ ment, while, on the other hand, the lesions present in Case III (Figs. 2 and 3) are evidently very old, as evidenced by the extensive coagulation necrosis and the reactive fibrotic condition in the immediate neighborhood. Summary'. We have given clinical and pathological proof of the occurrence of cases of ascending rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1928
1928
1987
1987

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…He inferred that the output of the heart was diminished. A similar decrease after a similar dose was found by Sturgis, Wearn and Tompkins (6) in patients with effort syndrome.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…He inferred that the output of the heart was diminished. A similar decrease after a similar dose was found by Sturgis, Wearn and Tompkins (6) in patients with effort syndrome.…”
supporting
confidence: 85%
“…The effect of atropine on systemic blood pressure has been studied by Harris (5) in normal adults and by Sturgis, Wearn and Tompkins (6) in patients with "effort syndrome." Harris observed that the subcutaneous injection of 1.2 mgm.…”
mentioning
confidence: 99%
“…Dr Francis Peabody with Dr Clough, Dr Sturgis, Dr Wearn, and Dr Tompkins reported that 65 soldiers with the "constitutionally inferior" type of the syndrome showed an abnormal rise in systolic blood pressure or pulse rate or both in response to an intramuscular injection of adrenaline.33 The same group without Peabody and Clough also administered an injection of atropine to these soldiers and noted that the rebound increase in pulse rate after an initial slowing Paul was greater in the patients than in the control subjects. 34 Adams and Sturgis found little evidence of a reduced vital capacity in the men,35 nor could they confirm the 1916 view of Lewis and his colleagues21 of any abnormality in the carbon dioxide combining capacity of the blood and in acid-base balance.…”
mentioning
confidence: 88%
“…It has been believed for years that the first action of this drug is to stimulate the cardio-inhibitor centre in the medulla oblongata. Various studies of different features of its action have demonstrated this, and it has been repeatedly shown that when the drug is injected subcutaneously the first result is beyond question a slowing of the pulse rate (Sturgis et al, 1919, McGuigan, 1921Harris, 1921 ;Platz, 1922). This result occurs even with doses of 2 mg. (Bain and Broadbent, 1949).…”
Section: Discussionmentioning
confidence: 97%